Some interesting fossils from the upper Paleozoic in Chaparra area, Southwest Peru - Yamagiwa, Nobuo (1979)
Four fusulinid species and one new coral species described in this article were found from the Upper Paleozoic at the south of Pampa Lobos, Chaparra area, Southwest Peru. Judging from the paleontological data, the present fossil assemblage indicates an early Wolfcampian age.